Search for the X (5568) State Decaying into Bs0 π± in Proton-Proton Collisions at s =8 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Escalante Del Valle, A.; Flechl, M.; et al. (My University, 2018)
A search for resonancelike structures in the Bs0π± invariant mass spectrum is performed using proton-proton collision data collected by the CMS experiment at the LHC at s=8 TeV, corresponding to an integrated luminosity of 19.7 fb-1. The Bs0 mesons are reconstructed in the decay chain Bs0→J/ψφ, with J/ψ→μ+μ- and φ→K+K-. The Bs0π± invariant mass distribution shows no statistically significant peaks for different selection requirements on the reconstructed Bs0 and π± candidates. Upper limits are set on the relative production rates of the X(5568) and Bs0 states times the branching fraction of the decay X(5568)±→Bs0π±. In addition, upper limits are obtained as a function of the mass and the natural width of possible exotic states decaying into Bs0π±.